Indianapolis Union and Belt Railroads - Darbee, Jeffrey T. (Book collections on Project MUSE., 2017)
"In an era dominated by huge railroad corporations, Indianapolis Union and Belt Railroads reveals the important role two small railroad companies had on development and progress in the Hoosier State. After Indianapolis was founded in 1821, early settlers struggled to move people was only a little over 14 miles. Though small in size, the Union and the Belt had an outsized impact, both on the city's rail network and on the city itself. It played an important role both in maximizing the efficiency and value of the city's railroad freight and passenger services and in helping to shape the urban form of Indianapolis in ways that remain visible today."--Provided by publisher.